Finanční analýza podniku - Capyková, Irena (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Bakalářská práce se zabývá finanční analýzou energetické společnosti E.ON, s. r. o. v letech 2008 – 2011. Práce je rozdělena na teoretickou a praktickou část. V teoretické části práce jsem uvedla metody finanční analýzy. V praktické části jsem blíže popsala společnost a následně vypracovala finanční analýzu. V závěru ze zjištěných údajů jsem provedla celkové zhodnocení situace podniku a doporučila návrhy pro další činnost.

The bachelor’s thesis deals with financial statement analysis of the energy producing and distributing company E.ON, s.r.o. in the time period from 2008 till 2011. The thesis is divided into two parts. The methods and tools for the financial analysis are introduced in the theoretical part. The second part of the thesis focuses on the company itself in details as well as it contains the elaboration of the company financial analysis. As a conclusion to this study the company financial assessment is carried out. Based on the assessment results the proposals for innovations are suggested.
The Financial Analyses of the Firm
Keywords: Finanční analýza; rozvaha; ukazatele likvidity; ukazatele rentability; ukazatel zadluženosti; výkaz zisku a ztráty; SWOT; Financial analysis; balance statement; liquidity ratios; profitability ratios; indebtedness ratios; profit and lost statement; SWOT.